Models of Grandparents’ Labour in the Socio-Economic Space of Russia - Bagirova, Anna P.; Shubat, Oksana M. (Economy of Regions, 2021)
Foreign researchers consider the phenomenon of grandparents’ labour in the framework of the economy of parental labour. Since the early 2000s, Russian scientists have been actively studying this problem due to high socio-economic disparity of Russian regions, and important strategic objectives stated in the Demography National Project and the Strategy of Spatial Development of the Russian Federation for the period until 2025. We identified and described specific regional situations, namely, models of grandparents’ labour in the socio-economic space of the country. To analyse grandparents’ labour, we examined individual questions of the “Comprehensive monitoring of living conditions” survey published by the Federal State Statistics Service (Rosstat). The research methodology includes both hierarchical (based on Ward’s method, the square of the Euclidean distance, and other measures) and non-hierarchical cluster analysis (the k-means method). We proposed a method for studying grandparents’ labour based on research of parental labour and international demographic studies on grandparenthood. The empirical analysis revealed 6 models of grandparents’ labour in the socio-economic space of Russia. These models differ in the level and intensity of involvement of older women in the sphere of grandparents’ labour and their potential in this area. For each model of grandparents’ labour, we identified the core regions (groups of regions) involved in the clustering. We explained why the government should be interested in the activation and stimulation of grandparents’ labour in Russian regions. Further research should focus on examining the particularities of grandparents’ labour depending on the actors: men, grandparents living with their grandchildren and apart from them, living in the same city, in the same or different regions of Russia.